Influence of composition diffusion on the band structures of InGaNAs/GaAs quantum wells investigated by the band-anticrossing model - Qiu, Y. N. (2009)
We investigate the influence of quantum-well intermixing (QWI) on the electronic band structure of GaInNAs/GaAs multiquantum wells. The band structures and optical transitions have been calculated based on the band-anticrossing (BAC) model and Fick's interdiffusion law for both intermixed and nonintermixed samples, respectively. The calculated results are consistent with the true optical transitions observed by photoluminescence excitation spectroscopy and secondary ion mass spectroscopy. Our investigation indicates that BAC model is valid for interdiffused quantum wells and verifies that the QWI process in GaInNAs/GaAs multiquantum wells is induced mainly by the interdiffusion of In-Ga between the quantum wells and barriers.